The effect of higher ambient air temperature on thermoregulatory responses and thermal sensation during lower body immersion in cool water - Wakabayashi, H.; Wijayanto, T.; Lee, J. Y.; Tochihara, Y. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The non-uniform thermal environment condition surrounding the human body will be observed during water exercise exposes upper body to the air. Although the effect of water on thermal responses is expected to be greater than air due to the higher thermal conductance of water, the combined effect of water and air temperature condition has not been sufficiently studied, and it will be useful information to conduct a water exercise program. This study investigated the effect of hot air temperature on thermoregulatory responses and thermal sensation during lower body immersion in cool water. METHODS: Nine male subjects were immersed in water to their chest level for 60 min at three water temperature conditions (Tw: 23, 26 and 33.5°C) with a neutral and hot ambient temperature (Ta: 27 and 31°C). Rectal temperature (Tre), skin temperatures, oxygen consumption (VO2), skin blood flow (SkBF) on the forearm and thigh, thermal sensation (TS), and thermal comfort (TC) were measured. RESULTS: No difference was observed in Tre, VO2, SkBF on forearm and thigh between hot and neutral Ta conditions during 23°C water immersion. In 26°C water, the SkBF on the forearm was significantly higher, and VO2 was significantly lower in hot Ta condition (p<0.05); Tre decrease was significantly greater in hot Ta condition compared to neutral Ta (p<0.05). TS and TC was significantly warmer and more comfortable in hot Ta condition than in neutral Ta condition during 26°C immersion (p<0.05), while the difference between Ta conditions was small in 23°C water, though colder TS and uncomfortable TC were observed in 23°C water compared to 26°C water. DISCUSSION: During lower body immersion in 23°C water, there was no difference in thermoregulatory responses and Tre between hot and neutral Ta condition. It suggests that cold stimulus from the lower body in 23°C water was large enough to induce thermoregulatory responses regardless of the effect from the upper body in the air. Although it was expected to maintain higher Tre if only the heat exchange on the skin surface was considered, in 26°C water, lower Tre was observed in hot Ta condition. Thermal input from the upper body in slightly hot Ta might suppress the shivering thermogenesis that led to lower Tre than in neutral Ta. The importance of Ta condition effects on shivering thermogenesis and Tre as well as thermal sensation was indicated during immersion, especially in a cool water environment of 26°, as in this study.